Modern architecture pop-up - Radevsky, Anton; Sokol, David M. (New York : Universe Publishing, 2008)
Showcases three-dimensional replications of some of the most innovative modern and contemporary architecture from around the world.
Aportes de Santiago Calatrava, I.M. Pei, Richard Meier, Frank Gehry, Zaha Hadid.
Contiene replicas tridimensionales de edificaciones modernas.
Keywords: ARQUITECTURA MODERNA; ARQUITECTURA -- DISEÑOS Y PLANOS